Learning Innovation Training Using Quizizz Based Google Meet for Elementary School Teachers: Pelatihan Inovasi Pembelajaran Menggunakan Google Meet Berbasis Quizizz Bagi Guru Sekolah Dasar - Wulandari, Fitria; Megawati, Fika; Tirtoni, Feri; Abrianto, Bagas; Rahayu, Fajarista Faiq (Procedia of Social Sciences and Humanities, 2022)
This Community Service activity aims to (1) provide knowledge and understanding of elementary school teachers about the Quizizzapplication (2) provide training to elementary school teachers in making assessments using the Quizizzapplication and implementing learning using google meetings, (3) providing training on the Quizizzapplication for students to elementary school teachers. In training the delivery of material and practice using an andragogy approach. Participants consisted of teachers at SD Muhammadiyah 5 Porong totaling 14 people. The delivery of material and practice in this training is carried out through workshop activities. The workshop was held in two meetings, the first was the delivery of the Quizizzapplication in general. The second is the practice of creating an account for teachers, setting language, creating quizzes and materials, how to do quizzes, how to give homework and Quizizz's interaction with google meetings. And how to create accounts for students, how students join classes, and how students take quizzes. With this training, the understanding and knowledge of teachers has increased as evidenced by the evaluation results. Teachers have been able to create quizzes and implement them in learning by using google meetings, and teachers understand how to apply Quizizzfor students.